Does union membership pay off? Evidence from Vietnamese SMEs - Nina Torm (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
In the absence of adequate institutional mechanisms, trade unions can potentially promote higher wages and other worker benefits, yet limited data availability means little is known about the effect unions have on individual earnings in developing economies. Using matched employer-employee data from 2013 and 2015 surveys, this paper examines the union wage premium among Vietnamese small and medium-sized enterprises. Controlling for firm and worker characteristics, the results show that unionized workers' wages are 9-22 per cent higher than those of non-union workers. The wage gain is substantially larger at the upper end of the wage distribution.
Keywords: C10; J31; J51; M52; O53; 330; union; wage; small and medium-sized enterprises; Viet Nam